Analysis of heart rate variation and foetal quiet sleep cycle correlation for normal and suspicious foetuses. Issue 4 (4th July 2018) - Li, Guangfei; Zhang, Song; Yang, Lin; Li, Shufang; Wang, Yan; Zhao, Yangyu; Yang, Yimin; Hao, Dongmei; Li, Xuwen; Zhang, Lei; Xu, Mingzhou
ABSTRACT: Cardiotocography (CTG) is the basic method of monitoring foetal condition in the perinatal period. However, due to the limited insight into the CTG generation mechanism, some CTG recordings can be mistreated as a predictor of neonatal asphyxia, leading to a wrong assessment of the foetal status and improper obstetric intervention. Therefore, in case of suspicious CTG indications, a reliable verification of the true foetal status is vital for reducing the clinical diagnosis false-positive rate and avoiding the unnecessary obstetrician intervention. The paper presents the results obtained for 44 foetuses on the shares of three heart rate variation (HRV) ranges and quiet sleep cycles. This approach uses the parameters of the HRV range shares and quiet sleep cycles to analyse different types of foetuses. The results obtained show that most parameters reveal significant differences between normal and suspicious groups. This is quite lucrative for defining a set of coefficients, whose incorporation into a classifier will improve the accuracy of distinguishing the normal foetuses from suspicious ones.